Renal Cell Carcinoma Clinical Management - Campbell, Steven C.; Rini, Brian I. (Current Clinical Urology, 2013)
Renal Cell Carcinoma: Clinical Management provides a comprehensive, state-of-the art review of this field, and will serve as a valuable resource for clinicians, surgeons and researchers with an interest in kidney cancer. The volume reviews new data about risk factors for the disease, profiles the new staging system for renal cell carcinoma (RCC), highlights our current understanding of familial syndromes of RCC and their molecular genetics, and provides new perspectives about imaging of renal tumors. For localized disease, a greater appreciation of nephron-sparing approaches and the importance of preservation of renal function is discussed in detail. Advances in surgical techniques are highlighted. For metastatic disease, the molecular biology of kidney cancer is reviewed in a concise and understandable manner, including the data that has fostered novel targeted approaches that have revolutionized management. The several landmark phase III targeted therapy trials published in the last few years are placed in context with respect to current management.